The Role of the Principal in Improving the Quality of Education - Sa’diyah, Lubabatus; Wahid, Mujahidah Mutiara; Khoiruna, Zuhda Ruchama (UM Purwokerto Press, 2025)
The quality of education in Indonesia is still a major concern in national development. One of the key factors influencing the quality of education at the educational unit level is the role of the principal. The principal not only carries out administrative functions, but is also required to be an instructional leader who is able to create positive changes in the school environment. This study aims to conceptually examine the role of the principal in improving the quality of education, with a focus on leadership, school management, and coaching of educators. This study uses a descriptive qualitative approach based on literature studies. Data sources were obtained from relevant literature, either in the form of books, scientific articles, or previous research results that discuss the topic of educational leadership and school quality management. The results of the study show that principals who apply a transformative and participatory leadership style are able to increase teacher work motivation, encourage learning innovation, and create a school culture that supports quality improvement. In addition, the principal's ability to supervise academics, formulate a strategic vision, and build partnerships with various stakeholders also determines the success of the education quality improvement program. The conclusion of this study confirms that the success of schools in achieving quality standards is highly dependent on the effectiveness of the principal's role. Therefore, strengthening the capacity of principals through ongoing training and policies that support school autonomy is an urgent need. This research is expected to be a reference in designing strategies to improve the quality of education based on school leadership.